2018
DOI: 10.1016/j.ram.2017.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Análisis MLVA y perfil de virulencia de aislamientos de Staphylococcus aureus resistentes a la meticilina adquiridos en la comunidad causantes de infecciones pediátricas en Paraguay

Abstract: Community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) is one of the first causes of skin and soft tissue infections, and can also produce severe diseases such as osteomyelitis and pneumonia. The aim of this descriptive study was to determine the SCCmec type and virulence profile and to study the genetic diversity by MLVA analysis of 21 CA-MRSA isolates that infected Paraguayan children in 2010. The SCCmec type and virulence factors were performed by PCR and genetic diversity by MLVA (multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The levels of penicillin resistance observed at the general level, whether the isolates were MRSA or MSSA, coincide with other regional and national studies that report levels of penicillin resistance in community S. aureus isolates greater than 90% in Latin America 21,[25][26][27] . Regarding the levels of resistance to clindamycin and erythromycin reported in this study (24% and 23%, respectively), a significant increase is seen, compared to reports made by our research group in previous studies in bacterial populations collected under the same conditions and geographical regions, but in different temporalities: in 2016, Guillén et al reported clindamycin and erythromycin resistance levels of 6.9% for both antibiotics and in 2020, Rodriguez et al reported clindamycin and erythromycin resistance levels of 15% and 17% respectively 25,27 .…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The levels of penicillin resistance observed at the general level, whether the isolates were MRSA or MSSA, coincide with other regional and national studies that report levels of penicillin resistance in community S. aureus isolates greater than 90% in Latin America 21,[25][26][27] . Regarding the levels of resistance to clindamycin and erythromycin reported in this study (24% and 23%, respectively), a significant increase is seen, compared to reports made by our research group in previous studies in bacterial populations collected under the same conditions and geographical regions, but in different temporalities: in 2016, Guillén et al reported clindamycin and erythromycin resistance levels of 6.9% for both antibiotics and in 2020, Rodriguez et al reported clindamycin and erythromycin resistance levels of 15% and 17% respectively 25,27 .…”
Section: Discussionsupporting
confidence: 85%
“…Other studies conducted by our research group, focused on the detection of coding genes of SEs A, B, C, D, and H, frequently associated with foodborne diseases, yielded carriage percentages for these genes lower than 5% 20,21 in samples collected from SSTI in the pediatric population, which reinforces the theory that these SE are strongly related to the production of gastrointestinal infections and those of the EGC cluster are present in all types of clinical samples and even in asymptomatic carriers 22 .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations